STRATEGI PENGELOLAN PANTAI LEMO SEBAGAI DESTINASI WISATA BAHARI DI LUWU TIMUR - Puspayanti, Nyoman Tri; Yanto, Subari; Patang, Patang (Universitas Negeri Makassar, 2019)
This study aims to find out how the management of Lemo beach is based on the current conditions and to determine the appropriate development strategy in the management of Lemo beach tourism, as a marine tourism destination in East Luwu. The research method is descriptive and quantitative. The types of research are field observations, questionnaires and literature studies, techniques and data collection instruments using observation techniques, questionnaires, literature and documentation and data analysis techniques using descriptive techniques and using SWOT analysis. namely visitors or tourists who are used as a source of information needed in research, while the object of research is Lemo Beach as a marine tourism destination. The results showed that from the SWOT Analysis, which uses the EFE Matrix, the IFE Matrix and SWOT Matrix external factors with the highest scores that affect the development of tourist objects are opportunity factors namely the chance of high tourist interest so Lemo beach can be a beautiful tourist spot, while the highest threat is negative impact of tourism. Internal factors with the highest score are strength factors, namely natural potential that supports tourism activities, cool and beautiful air, while the weakness factor is lack of awareness of the environment.